2011
DOI: 10.2466/15.22.pms.112.3.783-798
|View full text |Cite
|
Sign up to set email alerts
|

Change in Dexterity with Sensory Awareness Training: A Randomised Controlled Trial

Abstract: The role of sensory awareness in movement control is receiving increasing interest in sports and clinical literature as a feed-forward and feedback mechanism. The aim of the study was to assess the feasibility and effect of training in sensory awareness on dexterity in healthy adults. 29 healthy students were randomly allocated to a single-group, sensory awareness lesson with the dominant hand, the same lesson with the nondominant hand, or to a sham control group. Dexterity measures included the Purdue Pegboar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Publication dates ranged from 1991 [ 12 ] to 2014 [ 25 ]. Populations under investigation in the included RCTs ranged from healthy volunteers [ 6 , 12 , 15 17 , 19 , 24 ], healthy ageing [ 21 23 ], institutional ageing [ 25 ], people with multiple sclerosis [ 7 11 , 13 ], eating disorders [ 14 ], myocardial infarct [ 18 ], and sleep bruxism [ 20 ]. Studies generally had small sample sizes with a mean of 40.8 participants (SD 23.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication dates ranged from 1991 [ 12 ] to 2014 [ 25 ]. Populations under investigation in the included RCTs ranged from healthy volunteers [ 6 , 12 , 15 17 , 19 , 24 ], healthy ageing [ 21 23 ], institutional ageing [ 25 ], people with multiple sclerosis [ 7 11 , 13 ], eating disorders [ 14 ], myocardial infarct [ 18 ], and sleep bruxism [ 20 ]. Studies generally had small sample sizes with a mean of 40.8 participants (SD 23.5).…”
Section: Resultsmentioning
confidence: 99%
“…Single randomised controlled studies reported statistically significant, positive benefits compared to control interventions and included the following: greater neck flexion and less perceived effort after a single FM lesson for neck comfort [ 6 ]; reduced prevalence of neck pain and disability in symptomatic women after FM (individual and group sessions compared to conventional care or home exercises) [ 8 ]; reduced perceived effort in FM group for people with upper torso/limb discomfort [ 13 ]; improved balance in people with MS after eight FM sessions [ 9 ]; improved body image parameters in people with eating disorders after a nine-hour FM course [ 14 ]; reduction in nocturnal bruxism in young children after 10-week course of FM lessons [ 20 ]; improved dexterity in healthy young adults after a single session of FM class [ 24 ]. …”
Section: Resultsmentioning
confidence: 99%
“…As this is the first study investigating sensory awareness training in this context, we do not know how much time would be required to see a measurable change on the chosen tests. In a previous study [4], sensory awareness training of 40 min resulted in significant improvements on the PP and Grip-Lift task. However, this may be the consequence of immediate testing and does not represent lasting change.…”
Section: Discussionmentioning
confidence: 94%
“…Following this, testing was undertaken with the following tests in order: PP, Grooved Pegboard Test (GPT) [10] and the Grip-Lift task. There is a lack of precedent from which to accurately calculate a sample size, however a sample size for 80% power and based on an effect size of 0.75 for the PP in Bitter et al [4] suggests 29 participants per group. All participants provided written, informed consent, in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation